A novel beamforming method for array antennas integrating Extended maximum power transfer efficiency and Genetic algorithm - Song, Shihang; Ding, Guowen; Luo, Xin-Yao; Wang, Shen-Yun (International journal of electronics and communications, 2025)
This paper presents a novel beamforming method for array antennas that integrates the Extended Maximum Power Transfer Efficiency (EMMPTE) technique with the Genetic Algorithm (GA). This approach achieves both maximum power transfer and significant precision in energy distribution across multiple beams. The process starts with extracting the far-field electric field parameters of the antenna array. The EMMPTE technique is then used to maximize efficiency in the target beam direction. To ensure accurate energy control between beams, specific constraints are introduced, and the GA is employed to handle the complex requirements of beamforming, efficiency optimization, and energy distribution control simultaneously. This method’s innovation lies in its dual ability to maximize power transfer while precisely controlling energy distribution under complex constraints. The method was validated using a dual-substrate linearly polarized patch antenna array for the 5G frequency band (3.3–3.6 GHz). Experiments with dual-beam and triple-beam configurations showed that the method allows precise control of individual beams in multi-beam scenarios. The simulation results closely match experimental measurements, confirming the method’s effectiveness.